POSSIBLE COMPLICATIONS OF LIPOSUCTION: AN INTEGRATIVE REVIEW (CIPEEX, 2025)
Introduction: Liposuction is a cosmetic surgical procedure aimed at reshaping and defining body contours by removing localized fat deposits. During liposuction, fat is aspirated using cannulas inserted through small incisions in the skin. Although it is considered a minimally invasive surgery, liposuction can result in complications that should be considered before undergoing the procedure, including fat embolism syndrome.Objective: To describe the main complications of liposuction, highlighting fat embolism.Methodology: To conduct this integrative literature review, articles obtained from virtual databases (PubMed and SCIELO) were utilized. For the bibliographic survey, Descriptors in Health Science (DeCS) “Postoperative Complications,” “Fat Embolism,” and “Lipectomy” were used, covering the years from 2011 to 2021.Results: Complications of cosmetic liposuction can be divided into local (hematomas and seromas, infections, skin necrosis, contour irregularities, and skin sensitivity changes) and systemic (venous thromboembolism, cardiac changes, allergic reactions, and fat embolism). According to the studies analyzed, fat embolism warrants greater attention compared to other complications because, although rare (0.001-0.005%), it is potentially fatal and often requires intensive treatment. In these cases, fat enters the bloodstream and can cause pulmonary (81%), neurological (32%), and cardiac (22%) issues, presenting symptoms such as dyspnea, tachycardia, confusion, dizziness, arrhythmias, and tachycardia, which may progress to death. It is also concluded that large-volume liposuction surgeries and gluteal injections present risks of more severe complications (such as fat embolism), whereas traditional liposuction may have milder symptoms. However, liposuction is a safe surgical procedure when performed by a qualified and experienced plastic surgeon in an appropriate setting.Conclusion: It is concluded that careful selection of the surgeon, preoperative testing, adherence to pre- and postoperative guidelines, and open communication with the surgeon are essential measures to minimize risks and ensure a satisfactory outcome.
Keywords: postoperative complications; fat embolism; lipectomy